Building Supervisory Structures in Sub-Saharan Africa : An Analytical Framework - Quintyn, Marc (IMF Working Papers; Working Paper ;, 2007)
Current trends in financial sector development in sub-Saharan Africa are prompting policymakers to focus on the design of appropriate supervisory structures. Against the backdrop of worldwide efforts to remodel supervisory structures, this paper develops an analytical framework for designing a regulatory strategy that could assist in prioritizing the needs for regulation and supervision over time. Such a strategy should facilitate the design of a supervisory structure suitable for an individual country's current and future needs. The paper emphasizes that in the case of sub-Saharan Africa, any such strategy is constrained by the reality of capacity limitations and should take into account the need to keep the central bank involved in the process. Building on the framework, the paper identifies a number of supervisory structures that could meet sub-Saharan Africa's needs.